STRATEGI PENGEMBANGAN USAHA KERAJINAN KAIN SONGKET DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI NAGARI PANDAI SIKEK KECAMATAN X KOTO KABUPATEN TANAH DATAR - Deby Meisya Adisty; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
The background of this research is about the strategy for developing a songket craft business in improving the community's economy due to limitations or problems in songket woven crafts in the production process which is still done manually so that it reduces the production of songket crafts, and decreases the production of songket crafts which results in decreased income. The type of research used is qualitative research, and the object of research is the Pandai Sikek songket business. Collection of data obtained through observation, interviews, and literature study. And for technical data analysis using SWOT analysis. The stages are passed by identifying internal factors and external factors through interviews, and then using the IFE Matrix, EFE Matrix, SWOT Matrix and through the Weight Score Table Analysis. From the results of the data analysis carried out, the score for each factor was obtained, namely the weight of the strength score of 1.46, the weight of the weakness score of 1.06, the weight of the opportunity score of 1.4 and the weight of the threat score of 1.1. From the results of these data, the total weight value in the IFAS matrix is 2.52 and the EFAS matrix is 2.5.